Market diversification to increase the demand for and value of Bangladeshi shrimp - van der Pijl, Willem (International Food Policy Research Institute, 2024)
In a rapidly growing global shrimp industry, Bangladesh’s shrimp sector faces fierce competition from much larger producers such as Ecuador, India, and Vietnam. One of Bangladesh’s challenges is that it is overdependent on Europe's fragmented hotel, restaurant, and catering (HoReCa) segment and ethnic retail markets, where it exports 88 percent of its output. This market is highly price-driven and limited in size. However, Bangladesh’s exporters have no or only limited access to retail markets in the European Union (EU), the United States (US), or other markets that source black tiger shrimp due to a lack of high-quality products, a lack of Aquaculture Stewardship Council (ASC) and Best Aquaculture Practices (BAP) certification, negative market perception of the country’s shrimp, and a lack of promotional activities. As a result of the increased competition and restricted market access, Bangladesh’s exporters and farmers are experiencing spiraling prices, and their future activities are at risk. Diversifying its markets should help the industry increase demand and get better prices for the products it exports. This brief explores the current market position of Bangladeshi shrimp and what the country can do to diversify its markets. Promotion is key, but not to consumers. Business-to-business (B2B) shrimp buyers worldwide must view Bangladesh as a reliable source of competitive, high-quality, sustainable shrimp.